Analisis Literasi Matematika Menggunakan Mind Mapping dalam Pembelajaran Matematika - Wardhany, Alif Fiana Puspa; Hidajat, Djatmiko; Farahsanti, Isna (Universitas Nusantara PGRI Kediri, 2024)
One of the effective strategies to measure students' mathematical literacy is the mind mapping approach to education. The purpose of this study was to describe the mind mapping model on flat building materials in improving students' mathematical literacy. The approach method used was descriptive qualitative, this study surveyed 21 sixth grade students of SMP Penda Tawangmangu, with three samples selected to reflect high, medium, and poor performance. The strategies used were interviews and test questions. Data analysis procedures included data collection, data reduction, data presentation and conclusions. Three indicators were met by four students in the high mathematical literacy ability category, thirteen by students in the medium mathematical literacy ability category, although the level of completeness and accuracy was lower, and four by students in the low mathematical literacy ability category.